Digital Transformation in MSMEs: an Overview of Challenges and Opportunities in Adopting Digital Technology - Sri Hariyanti; Desi Kristanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital transformation has become an important key in driving global economic growth, especially for Micro, Small and Medium Enterprises (MSMEs) in Indonesia. In the face of increasingly fierce global competition, MSMEs need to take advantage of the opportunities offered by digital transformation to remain relevant and competitive. Although there are challenges such as digital literacy, access to technology, and data protection, MSMEs can overcome these through awareness of data security and implementing best practices in information management. By adopting digital technology, MSMEs can expand market reach, increase operational efficiency and optimize business decision making. A comprehensive strategy for overcoming challenges and exploiting digital opportunities is needed, such as the development of a digital transformation plan that involves concrete steps to achieve business goals through digital platforms. Through understanding the concept of digital transformation and applying descriptive qualitative methods, MSMEs can make optimal use of digital technology to increase competitiveness, expand markets, increase income and reduce operational costs. With full support from stakeholders, MSMEs in Indonesia have a great opportunity to develop and survive in this digital era.